The Economic Efficiency of Buffalo Business (Bubalus Bubalis) With the Shepherd - Rusdiana, Supardi; Praharani, Lisa; Sianturi, Riasari Gail (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Buffalo has a very big role to the family economy of stockbreeders. But until now, buffalo business in Banten Province is still small, and has not led to commercial business. The research was conducted in Cibarani Village, Cisata District, Pandeglang Regency, Banten in 2016. This study used interview and questionnaire filling methods to the 24 buffalo breeders. By accidental sampling, sampling of respondents was found in the cage, house, paddy field and fields. Primary data were obtained from stockbreeders and secondary data were obtained from the local institution. Primary and secondary data were analyzed descriptively, quantitatively, t-test analysis and economic analysis. The aim of this research was to determine the economic efficiency of buffalo business (bubalus bubalis) with the shepherds in stockbreeders. The results showed that, the factors that influenced the increased economic efficiency of buffalo business in breeders had a significant effect on (P <0.05) to the breeders profits variable. The female buffalo business by breeding, breeders' profits was Rp.7.889.000 / year, with R / C 1.02 higher. The male buffalo business by fattened up, breeders’ profits amounting to Rp.7.575.000 with R / C of 1.05 lower. The buffalo business in breeders by shepherded, through male fattened up or breeding, was economically worth to try.